The Influence of Internal Communication and Non-Physical Work Environment on Employee Productivity - Ade Febrianto; Rio Nardo (CAKRAWALA : Management Science Journal, 2025)
This study aims to analyze the influence of internal communication and non-physical work environment on employee work productivity. The method used is a quantitative method with data collection techniques through observation and questionnaire dissemination. The research population consists of 63 employees of the Bogor Regency Manpower Office who come from the secretariat sector, the field of placement and transmigration of job training, the field of training and work productivity, and the field of industrial relations and working conditions. This study uses a total sampling technique, where the entire population is used as a research sample. This study concludes that the work productivity of employees of the Bogor Regency Manpower Office is partially and significantly influenced by internal communication and non-physical work environment. Effective internal communication improves performance while a conducive non-physical work environment encourages employee comfort and motivation.